2018
DOI: 10.18203/2394-6040.ijcmph20180950
|View full text |Cite
|
Sign up to set email alerts
|

Study to assess knowledge, attitude and practice regarding organ donation among interns of a medical college in Telangana, India

Abstract: Background: There is a gradual decrease in health status and daily functioning in patients with end stage organ failure and timing of death remains uncertain. Organ transplantation is the only cure to such patients. Organ donation rate in India is only 0.26 per million. This is due to lack of awareness about the need of organ donation and the ignorance of common men and medical fraternity about the importance, procedures, benefits and legal issues of organ donation. The objective of this study is to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 7 publications
9
22
1
Order By: Relevance
“…In the present study, among the participants who did not want to become a donor, 45.4% gave a reason of "Fear of Organs being misused", a similar figure was observed in a study done by Jothula et al and Vaishalay et al 7,9 In regard to the above statement made, another question was asked about the act formulated to regulate the transplantation, 19% knew that there is some act regarding transplantation but only 10% named the Act as "Transplantation of Human Organs Act 2014". There is a government scheme named "Jeevandan" regarding Transplantation of Organs started by Andhra Pradesh state prior to 2014, only 3.9% respondents knew about it, on the contrary at least 41% knew about it in the study conducted by Jothula et al 7 Few other studies showed that the pattern of knowledge about legislative regulations about organ transplantation and government schemes (or organisations) was 73% by Sucharitha et al, 78% by Dardevessis et al, 72% by Dasgupta et al [13][14][15] The present study showed that most (67.8%) of participants were willing for organ donation which was similar to the findings of Shah et al (62%). 8 There were varied results observed in few other studies about willingness, 43% by Vaishaly et al, 53% by Sucharitha et al, 73% by Annadurai et al and 47% in rural Kerala by Manojan et al 9,12,13,16 People always have expectations from the person to whom they donated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, among the participants who did not want to become a donor, 45.4% gave a reason of "Fear of Organs being misused", a similar figure was observed in a study done by Jothula et al and Vaishalay et al 7,9 In regard to the above statement made, another question was asked about the act formulated to regulate the transplantation, 19% knew that there is some act regarding transplantation but only 10% named the Act as "Transplantation of Human Organs Act 2014". There is a government scheme named "Jeevandan" regarding Transplantation of Organs started by Andhra Pradesh state prior to 2014, only 3.9% respondents knew about it, on the contrary at least 41% knew about it in the study conducted by Jothula et al 7 Few other studies showed that the pattern of knowledge about legislative regulations about organ transplantation and government schemes (or organisations) was 73% by Sucharitha et al, 78% by Dardevessis et al, 72% by Dasgupta et al [13][14][15] The present study showed that most (67.8%) of participants were willing for organ donation which was similar to the findings of Shah et al (62%). 8 There were varied results observed in few other studies about willingness, 43% by Vaishaly et al, 53% by Sucharitha et al, 73% by Annadurai et al and 47% in rural Kerala by Manojan et al 9,12,13,16 People always have expectations from the person to whom they donated.…”
Section: Discussionsupporting
confidence: 89%
“…In this cross-sectional study, it turns out that 100% of the participants have heard term organ donation which was similar to the study done on medical students by Jothula et al (100%) and study done on college of commerce students by Shah et al (87.5%). 7,8 Media is said to be the best mode to get in touch with the society and students in this study have heard about organ donation mostly from television(66.3%) and newspapers (56%). Similar results have been found in a study conducted on patients and their attendants in the outpatient department of Dr. DY Patil Medical College, Pune by Vaishalay et al 9 A study conducted by Khalil et al showed that television drama helps in propagation about health information and organ donation.…”
Section: Discussionmentioning
confidence: 83%
“…In the present study, all of the 1 st MBBS students had adequate knowledge about organ donation (adequate means more than 50% knowledge). It is similar to study done by Kishore Jothula et al (Jothula & Sreeharshika, 2018). All the participants had heard about organ donation.…”
Section: Discussion:-supporting
confidence: 85%
“…The reasons for this pathetic scenario may be the ignorance of common public about the importance, procedures, benefits and legal issues of organ donation (Ilango et al, 2014). A study stated that even medical fraternity was lacking clarity with regards to the rules and procedures related to organ transplantation (Jothula & Sreeharshika, 2018). This emphasizes that providing adequate knowledge regarding organ donation in the community is the need of the hour.…”
mentioning
confidence: 99%
See 1 more Smart Citation